An Analysis of Contemporary Chinese Marriage and Family Conditions Based on Biblical Perspectives on Marriage and Family - HE, Zhangrong (Journal of Research for Christianity in China (JRCC), 2025)
Since the reform and opening up, the traditional marriage form is disappearing in two major ways. One is the structure of marriage and socializa- tion of marriage ability. Thus, what could we get back the traditional value of the marriage? The is not only the book which talks about religion, but also talk about the  many social ethic, such as , sexual, marriage, single, devoice. And presence of couples. In this article, according to the studies of bible, its will show that the reason why men and women should marry each, the principle of the marriage, the condition of devoice and how to deal with the marriage life.